Community Empowerment Based on Asset- Based Community Development in Enhancing Environmental Awareness and Income of Forest Farmer Groups - Putra, Tri Cahyono; Septiarti, Serafin Wisni (Universitas Muhammadiyah Malang, 2026)
This research aims to (1) describe of forest farmers empowerment, (2) analyze changes in forest farmers behavior in management and preserving forest ecosystems as a result of empowerment activities, and (3) analyze the contribution of local resource-based empowerment to increasing the income and economic independence of forest farmers. This research used a qualitative method with a case study approach involving forest farmers on the slopes of Mount Arjuno in Dayurejo Village, Prigen District, Pasuruan Regency, East Java, specifically the Forest Farmer Group (KTH) under the auspices of the Loka Jaya Binangun Village Forest Management Institution (LPHD). Primary data were obtained through in-depth interviews, focus group discussions, and participant observation, while secondary data were collected through document analysis. Data validity was ensured through triangulation. Data validity was ensured through triangulation by collecting data from different sources and at different times. The data were processed and analyzed by grouping and integrating predetermined categories, which were then described and interpreted to draw conclusions. The results indicate that first, forest farmer empowerment in forest management emphasizes informal and participatory approaches, such as direct field practice, group discussions, community service activities, and experiential learning, rather than instructive and formalistic methods. Second, Behavioral change occurs effectively through a gradual process involving direct experience, collective practice, and learning based on real-life needs, transforming forest farmers’ perspectives and behaviors from passive and short-term forest management toward active, planned, and sustainability-oriented forest management. Third, environmental awareness is developed through lived experiences rather than coercive regulations. This contextual empowerment approach grows organically through shared practice and field-based learning, making the model adaptive to the local social-ecological context and the dynamics of cooperation among stakeholders, while maintaining the forest farmer group as the central actor in forest management.